Uma revisão crítica sobre o estado burocrático-autoritário: comparando a experiência brasileira e chilena - Livacic, Gastón Ernesto Passi (2016)
This paper aims to propose a discussion about the core elements of bureaucratic- authoritarian state theory of the argentine political scientist Guillermo O'Donnell. Analyzing the economic and political interpretations that permeate their way of thinking and the resulting implications in power relations caused by the economic structuring approach. The historical cases traversed by this kind of rule will be examined, overall, through the concepts and correlations, which allow the direction for the bureaucratic - authoritative forms, likewise the post- strokes standards to allow consideration the dynamic power compared to such types. In particular, comparing disaggregated the standards set in the experiences Brazil and Chile. The nodal axis of this research seeks to reframe the political, economic and institutional trajectory explained the theory of bureaucratic- authoritarian state reflecting on the types of conflicts arising in this type of domination as well as discussing fundamentally the place of common development derived from the economic structure accumulative proposed by the author .